Morphological Study on Age Related Changes of Prostate (Bangladesh Journal of Anatomy, 2010)
Context: Prostate related clinical conditions such as prostatic benign hyperplasia and carcinoma prostate are major medical conditions within aging population. Detailed morphological knowledge is essential for proper diagnosis and management of prostatic disease. Study design: Descriptive type of study. Place and Period of study: Department of Anatomy, Dhaka Medical College, Dhaka from August 2006 to June 2007. Materials: Present study was performed on 70 post mortem human prostate. The samples were collected from unclaimed dead bodies that were under examination in the Morgue of Department of Forensic Medicine of Dhaka Medical College, Method: The samples were divided into three age group; Group A (10-20 years), Group B (21-40 years), Group C (41-70 years). All samples were studied morphologically. Result: Statistically significant positive correlation was found between age and weight, length, transverse diameter, antero-posterior diameter of prostate. Conclusion: There were changes in the morphology of prostate in relation to age. Keywords: Prostate; morphology. DOI: 10.3329/bja.v7i2.6085 Bangladesh J. Anat. 2009; 7(2) : 68-72